Find solutions to your problems with the help of IDNLearn.com's knowledgeable users. Receive prompt and accurate responses to your questions from our community of knowledgeable professionals ready to assist you at any time.

Express the function as a composition of two simpler functions.

[tex]\[ y = \sqrt{x^{19} + 9} \][/tex]

Select each pair of functions that result in the given function:

A. [tex]\( u = x^{19} + 9 \)[/tex] and [tex]\( y = \sqrt{u} \)[/tex]

B. [tex]\( u = x + 9 \)[/tex] and [tex]\( y = \sqrt{u^{19}} \)[/tex]

C. [tex]\( u = \sqrt{x} \)[/tex] and [tex]\( y = u^{19} + 9 \)[/tex]

D. [tex]\( u = x^{19} \)[/tex] and [tex]\( y = \sqrt{u + 9} \)[/tex]

E. [tex]\( u = \sqrt{x + 9} \)[/tex] and [tex]\( y = u^{19} \)[/tex]


Sagot :

To express the function [tex]\( y = \sqrt{x^{19} + 9} \)[/tex] as a composition of two simpler functions, we need to find functions [tex]\( u \)[/tex] and [tex]\( y \)[/tex] such that [tex]\( y \)[/tex] is expressed in terms of [tex]\( u \)[/tex]. Essentially, we want to split the original function into two functions where one depends on [tex]\( x \)[/tex] and the second depends on the first function.

Given the original function:
[tex]\[ y = \sqrt{x^{19} + 9} \][/tex]

We will check each pair of simpler functions to see if they correctly decompose this function.

1. [tex]\( u = x^{19} + 9 \)[/tex] and [tex]\( y = \sqrt{u} \)[/tex]
[tex]\[ u = x^{19} + 9 \quad \Rightarrow \quad y = \sqrt{u} = \sqrt{x^{19} + 9} \][/tex]
This pair is valid because substituting [tex]\( u \)[/tex] into [tex]\( y \)[/tex] results in the original function [tex]\( y = \sqrt{x^{19} + 9} \)[/tex].

2. [tex]\( u = x + 9 \)[/tex] and [tex]\( y = \sqrt{u^{19}} \)[/tex]
[tex]\[ u = x + 9 \quad \Rightarrow \quad y = \sqrt{u^{19}} = \sqrt{(x+9)^{19}} \][/tex]
This pair does not match the original function because [tex]\( \sqrt{(x+9)^{19}} \neq \sqrt{x^{19} + 9} \)[/tex].

3. [tex]\( u = \sqrt{x} \)[/tex] and [tex]\( y = u^{19} + 9 \)[/tex]
[tex]\[ u = \sqrt{x} \quad \Rightarrow \quad y = u^{19} + 9 = (\sqrt{x})^{19} + 9 = x^{9.5} + 9 \][/tex]
This pair does not match the original function because [tex]\( x^{9.5} + 9 \neq \sqrt{x^{19} + 9} \)[/tex].

4. [tex]\( u = x^{19} \)[/tex] and [tex]\( y = \sqrt{u + 9} \)[/tex]
[tex]\[ u = x^{19} \quad \Rightarrow \quad y = \sqrt{u + 9} = \sqrt{x^{19} + 9} \][/tex]
This pair is also valid because substituting [tex]\( u \)[/tex] into [tex]\( y \)[/tex] results in the original function [tex]\( y = \sqrt{x^{19} + 9} \)[/tex].

5. [tex]\( u = \sqrt{x + 9} \)[/tex] and [tex]\( y = u^{19} \)[/tex]
[tex]\[ u = \sqrt{x + 9} \quad \Rightarrow \quad y = u^{19} = (\sqrt{x + 9})^{19} = (x + 9)^{9.5} \][/tex]
This pair does not match the original function because [tex]\( (x + 9)^{9.5} \neq \sqrt{x^{19} + 9} \)[/tex].

Thus, the pairs of functions that correctly express [tex]\( y = \sqrt{x^{19} + 9} \)[/tex] are:

[tex]\[ u = x^{19} + 9 \quad \text{and} \quad y = \sqrt{u} \][/tex]

[tex]\[ u = x^{19} \quad \text{and} \quad y = \sqrt{u + 9} \][/tex]

These pairs decompose the original function as desired.